Reinventing talent management: How to maximize performance in higher education - Ramaditya, Muhammad; Maarif, Mohamad Syamsul; Affandi, Joko; Sukmawati, Anggraini (Frontiers in Education, 2022)
Talent management is considered a new organizational priority in managing people that both academicians and practitioners discuss. The purpose of this research was to examine the role of talent management (TM), knowledge management (KM), university transformation (UT), and academic climate (AC) in increasing the performance of private higher education institutions (PHEIs). This research applied a quantitative approach by collecting data from 382 lecturers who worked at various private universities in Indonesia. Online questionnaires were used to collect the data using a stratified random sampling method. Then these data were analyzed using Structural Equation Modeling–Partial Least Square. The findings indicated that systematic application of talent management and knowledge management, university transformation, and academic climate in PHEIs improves organizational performance. Developing a plan to transform their talent and the business process is the key to emphasizing its importance in shaping the character and quality of PHEIs. The practical implication, PHEIs must offer a conducive academic climate for talented lecturers. The study offers a value-add to the resource-based view theory, managing talent and knowledge as essential resources for organizational transformation to maximize organizational performance.